PTH-100 Psychological Morbidity and Provision of Psychological Support in the Inflammatory Bowel Disease Clinic. (4th June 2013) - Mankodi, S; Cronin, E; Greveson, K; Shepherd, T; Despott, E; Jaboli, M; Erian, G; Hamilton, M; Murray, C
Abstract : Introduction: Inflammatory bowel disease (IBD) can have a significant impact on physical, psychological and social wellbeing. We aimed to survey the impact of IBD on our patients' lives and their perceptions of psychological support use and availability. Methods: Inflammatory bowel disease (IBD) can have a significant impact on physical, psychological and social wellbeing. We aimed to survey the impact of IBD on our patients' lives and their perceptions of psychological support use and availability. Results: 6 patients were excluded as they had not completed the questionnaire. 94 patients were included (43 male, 51 female, average age 42 years, range 17–76). 46 had a diagnosis of Crohn's disease, 41 ulcerative colitis and 7 indeterminate colitis. Average disease duration for these patients was 15 years (range 1–51 years). Over the past 6 months 20 had symptoms constantly, 16 often, 17 occasionally, 10 sometimes, 13 rarely and 18 never. The average SIBDQ score was 48 (range 21–70). The average HAD score was 12.6 (range 0–33). When separated into HAD A (anxiety) and HAD D (depression) scores were 8.1 (range 0–18) and 4.8 (range 0–15) on average respectively, a score of 8 to 10 for either subscale being suggestive of the presence of the respective state. They were also asked which services they had previously used as forms of support. Of the 86 patients who answered this portion of the questionnaire, 13 (15%) said they had previously had counselling or psychological input, and 32 (37%) said they would like counselling or psychological input in the future if it was available. Conclusion: Our survey suggests there may be a higher rate of anxiety in patients with IBD, and that over a third of our patients would like access to psychological and counselling services if they were available. Psychological support is important to patients with IBD and should be incorporated into their management. Disclosure of Interest: None Declared.